WORD DETECTIVE AS AN EFFECTIVE STRATEGY FOR VOCABULARY MASTERY IN ENGLISH LANGUAGE TEACHING AND LEARNING - Ermayni Sari Nurdin (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2019)
This research is a quasi-experimental researchdesign.. This research aims find out the students’ vocabulary mastery taught by using Word Detective strategy, to find out the students’ vocabulary mastery taught without using Word Detective strategy, and to find out whether there is any significant difference on students’ vocabulary mastery taught by using and taught without using Word Detective strategy. It was done at Forestry Vocational School of Pekanbaru with the sample of research was the X Meranti as experimental class that consist of 34 students and X Meranti as control class that consist of 33 student. So, total sample of this research is 67 student. This reseach used T-test and SPSS 19 version. Result shows that experimental class or the class that treated with Word Detective Strategy gives a bigger score in posttest than in control class or a class. It means that Word Detective is an effective strategy for vocabulary mastery.